2017
DOI: 10.1074/jbc.m116.766469
|View full text |Cite
|
Sign up to set email alerts
|

Control of Amino Acid Homeostasis by a Ubiquitin Ligase-Coactivator Protein Complex

Abstract: Edited by James N. SiedowIntercellular amino acid transport is essential for the growth of all multicellular organisms, and its dysregulation is implicated in developmental disorders. By an unknown mechanism, amino acid efflux is stimulated in plants by overexpression of a membrane-localized protein (GLUTAMINE DUMPER 1 (GDU1)) that requires a ubiquitin ligase (LOSS OF GDU 2 (LOG2). Here we further explore the physiological consequences of the interaction between these two proteins. LOG2 ubiquitin ligase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…AIRP3 was identified as an interacting protein of UBC27. Previously, AIRP3 was shown to modulate high-salt and drought stress responses through ABA signaling by promoting the degradation of RD21 (37) and to modulate amino acid export by working as the coactivator of GLUTAMINE DUMPER1 (43,44). Here, we demonstrated that AIRP3 also physically interacts with UBC27 and ABI1 (Figs.…”
Section: Methodssupporting
confidence: 54%
“…AIRP3 was identified as an interacting protein of UBC27. Previously, AIRP3 was shown to modulate high-salt and drought stress responses through ABA signaling by promoting the degradation of RD21 (37) and to modulate amino acid export by working as the coactivator of GLUTAMINE DUMPER1 (43,44). Here, we demonstrated that AIRP3 also physically interacts with UBC27 and ABI1 (Figs.…”
Section: Methodssupporting
confidence: 54%
“…Agrobacteria strain AGL1 (gift from Charles Gasser, Department of Molecular and Cellular Biology, UC-Davis [ 48 ]) carrying vectors to express C-terminally YFP-tagged FRKs were co-infiltrated with AGL Agrobacteria carrying P19 (gift from Richard Michelmore, Plant Sciences Department, UC-Davis [ 49 ]) into Nicotiana benthamiana leaves. After 48 h, a small leaf disc close to the site of infiltration was excised and then prepared and mounted similarly to what was shown in Littlejohn and Love [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms by which CSE promotes vasodilation at the maternal-fetal interface likely involve eNOS. Protein cysteine residues are susceptible to oxidation [ 62 , 63 ], and preeclamptic placentae feature increased eNOS oxidation and decreased NO synthesis [ 15 ]. This suggests that uterine artery CSE deficiency could promote preeclampsia via higher oxidative stress and eNOS inactivation.…”
Section: Discussionmentioning
confidence: 99%